User Involvement and Performance of Enterprise Resource Planning System Implementation in Multi-national Organizations in Kenya. A Case of Un-Habitat in Kenya - Ngala, Derrick (Asian Journal of Research in Computer Science, 2021)
Most multi-national organizations in Kenya are adopting an entire suite of enterprise resource planning Software and customize them to fit the business processes. Despite the continued review of the enterprise resource planning suite, the realization of a successful enterprise resource planning implementation for multi-national organizations is becoming difficult, owing to user involvement issues. This research, therefore, addressed this by assessing the effect of user involvement on enterprise resource planning implementation for multi-national organizations in Kenya. The study used a descriptive research design, where it obtained a sample size of 70 respondents and selected the respondents from 85 subjects using stratified proportionate sampling. The data for the study was gathered from primary sources using a questionnaire. Data was evaluated using quantitative analysis to provide descriptive statistics accompanied by inferential analysis to estimate the model. Guided by the study findings, it was concluded that; there is a positive and significant relationship between users’ functional requirements activities and enterprise resource planning implementation; users’ presentation requirement activities positively significantly influence enterprise resource planning implementation, users’ quality assurance activities has a significant moderate influence on its enterprise resource planning implementation, and users’ project management activities have a significant moderate influence on enterprise resource planning implementation. The study recommends that these organizations should; develop users’ functional requirements activities policy, review policies on business processes to accommodate different system implementation practices; review current quality assurance activities by consumers to satisfy the planned enterprise resource planning system demand of the provider, and acquire as well as retain the appropriate users’ project management.